Carta de Roberto H. Todd a Benigno Fernández García - Todd, Roberto H.; Fernández García, Benigno (My University, 1935)
Cuenta en el Banco Scotia a favor de la Sra. Santos Raspaldo, viuda de Martínez Dávila.
Keywords: Martínez Dávila, Manuel A.,1883-1934; Porrata Doria, Adolfo; Rivera, Paco